Restraining air power : escalation management between peer air forces - Owen, Robert C., 1951- (Aviation and air power., 2022)
"Is it possible for two combatants who possess equally strong air forces to conduct limited warfare by restraining air operations? In Restraining Air Power, Robert C. Owen and contributing authors aim to answer this question by providing theoretical and empirical assessments of restrained air warfare through five historical case studies since 1945. Through an objective analysis of the past, this collection evaluates the principles of escalation and escalation management in conventional warfare scenarios to better understand when, why, and how peer opponents in past conflicts have expanded or restrained air operations. The surge in cyber warfare, the development of artificially intelligent weaponry, and the founding of the United States Space Force in 2019 mean that analysts and military planners must be prepared to think about escalation management and peer conflict in increasingly complicated and arduous ways. This comprehensive study provides readers with refined theoretical visions of the possibilities and challenges of managing escalation as a powerful mode of warfare between opponents who believe they must choose between sacrificing their own national interests or risking escalated destruction of their economies, military forces, and governing authority. The analysis within the pages of this volume updates our understanding of air warfare within a world of unprecedented military complexity and, as such, will hold immense value for specialists in advanced military studies as well as those studying international relations and history"--